The Teaching of Educational Material and Curriculum in the Sámi University College - Aikio, Aimo (Sámi dieđalaš áigečála, 2026)
The topic of my article is the issue of how teacher training practice can help with regard to the lack of educational materials made in the Sami language. The article is based on my own experiences as a lecturer in pedagogy at the Sami University College. I shall not deal with the issue of how to get more teaching materials into Sámi, but how existing materials can be used in a more holistic way in many different subjects and in a way that they will not become redundant quickly. I shall articulate what is the relationship between the curriculum, the use of curriculum and the needs of pedagogical materials. The aim of teacher training is to raise the professionalism of the teachers and to instruct as to how the curriculum is understood and used. The other intention of teacher training is to promote the teachers´ capability to make and use teaching materials with versatility. The themes which I have dealt with do not help to make more teaching materials available, but can remove the restrictions that exist as a result of the lack of these materials.